?EXTRACTION, SPECTROSCOPIC AND COLOURING POTENTIAL STUDIES OF THE DYE IN GINGER RHIZOME (ZINGIBER OFFICINALE) - POPOOLA , A. V.; IPINMOROTI, K. O.; ADETUYI , A. O.; OGUNMOROTI , T O. (Biological Sciences - PJSIR, 2022)
The dye in the rhizome of the plant, Zingiber officinale was extracted quantitatively using the solid-liquid extrac- tion method and its physico-chemical parameters as well as colouring potential studied. A lustrous, powdery brown dye melting point Ca. 88-90° of 13.90% yield was obtained. The dye was soluble in hydroxyl organic solvents and gave one homogenous component of R, value of 0.86 on chromatographic separation and a wavelength ofmaximum absorption A.m ••• 420run. The IR spectrum of the dye showed three major functional groups, ofOH group with broad band absorption between 3405-3120cm’ aliphatic or saturatedC-H stretching at2900-2880cm·1 and C=Opeakat 171O-1700cm·1whilst the presence of 1,4-disubstitution on benzene ring was observed at 1930-1880cm·l . Major proton absorptions on IH-NMR were observed at 7.2 ppm, 3.9 ppm and 1.2 ppm signifying the presence of benzyl, hydroxyl and ethyl protons at these respective absorptions. The dye gave a brilliant yellow colouration of light, wash and dry ironing (pressing) ratings of 5, 3 and 4 respectively on bleached cotton fabric.